INFLUENCE FACTORS OF MILLENNIAL’S INTENTION TOWARDS CASH WAQF - Setyowati, Hanik; Margarena, Agung Novianto; Ernawati, Dewi (Jurnal Syarikah : Jurnal Ekonomi Islam, 2024)
The purpose of this research is to identify the factors that can affect the low realization of Cash Waqf in Indonesia. This study uses a modified model of The Theory of Planned Behavior (TPB) by using the variables perceived efficacy, Muslim society, and accountability in the context of money endowments as a novelty of the study. This type of research is quantitative research and data collection uses an online questionnaire with a sampling technique using snowball sampling. This study involved 81 respondents in the city of Salatiga with data analysis using a simple regression through SPSS. The test results showed that both partially and simultaneously the three variables, namely perceived efficacy, Muslim society, and accountability, affect the interest of Millennial Cash Waqf in Salatiga City. This research suggests that the government through the Indonesian Waqf Board (BWI) should focus on strengthening the Islamic financial ecosystem through the development and increase of Cash Waqf contributions.